MANAGEMENT OF FINANCIAL RESOURCES OF COMMERCIAL BANKS - Xamidov Shaxriyor; Abduvahobov Shakhzod (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article elaborates on the issues, principles, and methods of managing the assets of commercial banks. The importance of asset management, types of assets, and key principles of bank asset management are discussed: liquidity, profitability, risk level, and the principle of diversification. Attention is paid to the problems that may arise in asset management and their solutions.